Improvement of IT infrastructure management by using configuration management and maturity models: a systematic literature review and a critical analysis - Serrano, J. P.; Pereira, R. (Organizacija, 2020)
Background and purpose: This research aims to investigate which benefits one may expect using Maturity Models in Configuration Management (CM) domain. CM is a support process that helps organizations have better management of their infrastructure. Its importance, in the Information Technology (IT) domain, has increased in recent years, despite this process not being technologically new, and the fact that many organizations implement this process in a haphazard way, which results in it not producing the benefits that it should produce. With the intention of assessing and improving the organizations' IT processes practices and capabilities, MMs have been developed and implemented. However, the application of MM in the CM domain is yet to be explored. Design/Methodology/Approach: Two Systematic Literature Reviews (SLRs) and a Critical Analysis were performed. In sum, 80 scientific articles of the most rated conferences and scientific journals were analyzed and conclusions were drawn. Results: This research concludes that despite the CM process being badly implemented, using a MM this process could decrease operational costs and increase the quality management of the infrastructure. Conclusion: However, no MM has been developed so far for the CM process practices. This MM would be a viable support tool for the IT organizations providers since this would help organizations have a mature CM process and better control of their IT infrastructure. Therefore, the existence of a MM for the CM domain would be a welcome advancement that should be developed in the future.